Effective Electrochemical Recognition of Tryptophan Isomers by MOF-Derived Chiral In2S3 Nanotubes. Issue 12 (1st December 2022) - Kuang, Rui; Deng, Ning; Dong, Fuying; Ding, Yongling; Kuang, Xuan
Abstract : Electrochemical enantiorecognition of Tryptophan (Trp) isomers using Cys@In2 S3 /GCE prepared by two steps of sulfidation and chiralization from MIL-68(In) is reported. The Cys@In2 S3 /GCE electrode shows highly selective, sensitive and quantitative analysis towards Trp enantiomers. This proposed chiral sensors could be considered for practical applications in the field of Trp related medical recognition.